Drip cooling of lactating sows - David A Nichols; James P Murphy; Robbins F Vic (Kansas Agricultural Experiment Station Research Reports, 1983)
Twenty eight sows and gilts were used to evaluate the value of drip sprinkling to reduce heat stress in lactating sows. Respiration rates for sprinkled sows were significantly lower than those of controls. Daily feed intake was significantly higher for wetted sows versus the unwetted controls. No differences were observed between groups on number of pigs born alive, dead, number weaned or pig birth weight.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Drip cooling; Lactating sows